Advances in understanding the pathogenesis of graft‐versus‐host disease. (6th October 2019) - Zeiser, Robert
Summary: Acute graft‐versus‐host disease (GVHD) remains a major complication after allogeneic haematopoietic stem cell transplantation (allo‐HSCT). The emergence of different immuno‐prophylaxis strategies, such as post‐transplant cyclophosphamide or anti‐thymocyteglobulin has reduced the incidence of acute GVHD in recent years. The biology of the acute GVHD we observe in the clinic may change due to the use of novel immuno‐stimulatory agents, including immune checkpoint inhibitors or anti‐neoplastic immune‐modifiers, like lenalidomide, given before or after allo‐HSCT. Here we discuss the recent advances in our understanding of acute GVHD with a focus on early events of the disease, including tissue damaging factors, innate immune cells, costimulatory pathways, immune cell signalling, immuno‐regulatory cell types, biomarkers of GVHD and regenerative approaches. New insight in the pathogenesis of acute GVHD has revealed the role of pro‐inflammatory intracellular signalling, defects in intestinal tissue regeneration and anti‐bacterial defence, as well as a reduced diversity of the microbiome, which will be the basis for the development of novel therapies.